A Comparative Study for Extracts of Celery (Apium graveolens L.) and Parsley (Petroselinum crispum Mill.) Plants and Some Physiological Parameters - Al-Shebani, Samah S. S. (Al-Qadisiyah Journal of Pure Science, 2017)
A pots experiment was conducted in the winter season (2014 - 2015) in a house garden in Al-Diwaniya city/ Al-Qadisiyah province to determine the physiological and chemical characteristics of the comparison between celery (Apium graveolens L.) and Parsley (Petroselinum crispum Mill.) plants. Plants were planted in a pots method at one date (12/01/2014) and 10 seeds per pot. All results under study were subjected for statistical analysis in order to know the significant differences between the traits by using F-test at 0.05. Results showed that all indicators germination of celery plant was morally superior to germinate parsley plant indicators, and the majority of physiological characteristics of the celery plant were morally superior to those of the parsley plant traits except number of leaves of the plant that showed its superiority in parsley plant. Leaves of celery plant content of phosphorus, total carbohydrates, moisture content, ash, sodium and iron content excellence on parsley plant was coupled with the recent leaves in the superiority of nitrogen, potassium, total protein, fat, calcium, zinc and copper content.